The John W. Knutson Distinguished Service Award in Dental Public Health-2002 Recipient Esther Colchamiro - David 1. Rosenstein, DMD, MPH, Professor and Chair, Department of Community Dentistry, Oregon Health (Blackwell Synergy, 2003)
Exactly 20 years ago, the first John Knutson Award was presented to David Ast. Ironically, I was the chair of the then Dental Health Section, which is now the Oral Health Section, and was honored to present Dr. Ast with the award. Since that time, the most influential people in the field of dental public health have received this award. All were giants in the field, some were legend. We had an individual almost solely responsible for the resurrection of the AAPI-ID